Engineering Altermagnetic Transitions in Two-Dimensional Metal–Organic Frameworks via Chemical Symmetry Breaking - Peibo Xu; Yixuan Che; Haifeng Lv; Xiaojun Wu; Jinlong Yang (Journal of the American Chemical Society, 2026)
Abstract Altermagnets are symmetry-defined magnetic phases that combine momentum-dependent spin splitting with zero net magnetization, offering promising opportunities for spintronics. However, their realization is strongly constrained by rigorous symmetry requirements. Exploiting the shared antiparallel magnetic order and vanishing net magnetization between antiferromagnets and altermagnets, we propose a general chemically driven strategy based on asymmetric ligand modification to transform pristine two-dimensional antiferromagnetic metal–organic frameworks into altermagnetic candidates. Using chromium phthalocyanine (CrPc) as a proof-of-concept model, we show that asymmetric modification lowers the local site symmetry at magnetic Cr centers and generates momentum-dependent spin splitting and anisotropic spin densities, as revealed by first-principles calculations. Oxygen-modified CrPc derivatives further illustrate the chemical tunability of this symmetry-control principle. Our work expands the design space of organic altermagnetic candidates and establishes a chemically grounded route for engineering symmetry-governed magnetic functionality in reticular materials.